Comparison of UV irradiance data from OMI with ground-based observations at the Chisinau (Kishinev) site, Moldova - Aculinin, Alexandr (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2012)
Erythemal UV irradiance data obtained from ground-based observations are used for validation of the UV products from overpass nadir measurements performed with the Ozone Monitoring Instrument (OMI) on-board the EOS Aura satellite platform. UV ground data were obtained with using of broadband radiometers (model UV-S-B-C) at the ground-based solar radiation monitoring station in Kishinev (Chisinau), Moldova during the period from 2004 to 2009. OMI UV final products were derived by the OMI’s international team with using of the TOMS-like algorithm. Erythemal dose rate at time of overpass (OEDR) and at local noon time (EDR@noon) and erythemal daily dose (EDD) were taken into analysis. Interval of 1-min averaging of erythemal UV irradiance measurements with ground-based broadband radiometer gives an possibility to make quasi-synchronous observations with OMI overpass measurements. Validation showed that OMI overpass UV data underestimate UV data from ground observations for all sky (AS) and cloud-free (CF) conditions. Results of validation showed a bias value of –15.8% under AS and –18.3% under CF conditions. Concerning EDR@noon data bias was –15.8% under AS and –17.7% under CF conditions; taking into account EDD data some increasing in bias was observed (with a value of –21.5% and –19.9% under AS and CF conditions, respectively). The effect of aerosols on UV irradiance was studied in terms of aerosol optical depth (AOD@340 nm) retrieved from the AERONET, NASA/GSFC. It was observed that there is a high correlation of ~0.79 and that a larger relative difference corresponds to a larger value of AOD@340 nm.